2016
DOI: 10.1002/pros.23204
|View full text |Cite
|
Sign up to set email alerts
|

Implications of High Rates of Metastatic Prostate Cancer inBRCA2Mutation Carriers

Abstract: BACKGROUND Patients with germline BRCA2 gene mutations (BRCA2mut) have more aggressive prostate cancer. Analysis of all reported germline BRCA2mut prostate cancer cases allows better understanding of the clinicopathologic features and survival outcomes of these men. METHODS A systematic review was performed with the MEDLINE database to capture articles evaluating clinicopathologic characteristics of men with BRCA2mut associated prostate cancer. Inclusion criteria were at least five subjects, confirmation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
3
7
0
Order By: Relevance
“…2b), and high expression of LIMK1 in prostate cancer indicates a poor outcome [23]. Germline DDR mutations, especially loss-of function BRCA2 mutations, are found primarily in prostate cancer presenting a more aggressive phenotype and a poor prognosis [24]. In our study, we found germline mutations in BRCA2, ATM, CHEK2, RAD50, and RAD50D, among which BRCA2 (5/7) harbored the most frequent germline mutation.…”
Section: Dna Damage Repair Pathwaysupporting
confidence: 48%
“…2b), and high expression of LIMK1 in prostate cancer indicates a poor outcome [23]. Germline DDR mutations, especially loss-of function BRCA2 mutations, are found primarily in prostate cancer presenting a more aggressive phenotype and a poor prognosis [24]. In our study, we found germline mutations in BRCA2, ATM, CHEK2, RAD50, and RAD50D, among which BRCA2 (5/7) harbored the most frequent germline mutation.…”
Section: Dna Damage Repair Pathwaysupporting
confidence: 48%
“…When compared with non-BRCA2 carriers, BRCA2 carriers had a significantly higher PPV of PSA >3.0 ng/mL (31% vs 18%; p=0.025), a higher PC incidence rate per 1000 person years (19.4 vs 12.0; p=0.03), a significantly higher frequency of intermediate-high risk PC (p=0.011) and were significantly younger at the time of PC diagnosis (p=0.044), with the youngest age of onset being recorded in a 41-year-old BRCA2 carrier. Overall, the results so far from the ongoing IMPACT study further substantiate the earlier age of onset and more aggressive PC phenotype seen in BRCA2 carriers which has been widely reported throughout the literature, 11,[31][32][33][34]36,87 and also highlights the efficacy of using PSA testing in this patient subgroup.…”
Section: Prostate Cancer Screening In Unaffected Brca2 Mutation Carrierssupporting
confidence: 74%
“…BRCA1 and BRCA2 gene mutations, confirmed to be linked to breast cancer in families [44, 45], confer a 3.8- and 8.6-fold increased risk of developing prostate cancer, respectively [14, 15]. BRCA2 carriers are associated with poor prognosis and more aggressive form in prostate cancer [46, 47]. In addition to BRCA1 and BRCA2 genes, previous studies supported the contribution of other undetermined genetic factors to the aetiology and prognosis of prostate cancer in breast cancer-prone families [4850].…”
Section: Discussionmentioning
confidence: 99%